Answers

2014-03-01T09:39:51+05:30
If x=1 is a common root of the equations a x^2 + a x + 3 = 0

Than, put 1 one the place of x we get,
1^2 + a. 1 + 3 = 0
=>1+a+3 = 0
=>a = -4

Again also, If x=1 is a common root of the equations x^2 + x + b = 0,
Than, put 1 one the place of x we get,
1^2 + 1 + b = 0,
=>1+1+b = 0
=>b=-2


so, ab = (-4)(-2) = 8 (ans)
0
i am pretty sure this is the process.
like he said, replace x with 1 because x=1 with bot equations
1) a1^2 + a1 + 3 = 0
a(1+1) + 3 = 0
2a = -3
a = -3/2

2) 1^2 + 1 + b = 0
2+b = 0
b = -2

ab= (-3/2)*(-2)
=3
how will i know that bro.....your a is far than x^2. i though its a equation rather than ax^2
than also its my fault...sorry
hahaha